The Application Of Processing Technology Of Assorted Chips For Optimizing Utilization Potential Local Resources - Imam Santoso (Journal of Innovation and Applied Technology, 2015)
ABSTRACTOne of the potential should be developed in the village Bakung are a variety of processing chips. Methods of activity in the introduction of this tech-nology package includes counseling, demonstration and practice. Extension activities or lectures intended to introduce a variety of matters related to the introduced equipment, process steps and various factors that must be considered in order to obtain quality treatment process-es in accordance with desired product. Demonstration activities conducted on the process of making chips in full by utilizing packet processing technology. In this demonstration activities presented in chronological order processing, process conditions that need to be considered and how to cope in every stage of the process when there are obstacles or problems with accompanying examples of product or process conditions with props. In the next activity, participants practice so as to operate the equipment are integrated in the production process.Implementation of science and technology activities has been well demonstrated by a whole series of programs that have been dlakukan. Some of the benefits of this activity is the increased understanding of the partici-pants in the activities of production and increasing the performance of its chips.Keywords: chipsprocessing, technology application